MARKET POWER DAN EFISIENSI INDUSTRI PERBANKAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Rifki Khairul Amri; Sofyan Syahnur (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
AbstractThis study aims to analyze the market power and efficiency of the banking industry on Indonesianeconomic growth from 2000-2015. This study only uses commercial bank data, not including BPR(rural credit banks) and Islamic banks. This study uses a multiple linear regression model with fourindependent variables, namely HHI (Herfindahl Hirshman Index), distribution of funds, commercialbank assets, inflation, and one dependent variable, economic growth as a dependent variable.Estimation results of this study show that market power and the efficiency of the banking industryhave a positive effect on economic growth. And inflation has a negative effect on economic growth.However, bank asset variable has no effect or is not significant on economic growth. This studyexpects that the government keeps encouraging the market power and efficiency of banking industrywith respect to the stability of economic growth with the low inflation rate.Keywords :Market power, Efficiency, Banking industry, Economic Growth